Light-emitting diode Disinfection as Continuous Room Surface Decontamination against Healthcare-Associated Pathogens. (4th October 2017) - Rutala, William A; Kanamori, Hajime; Gergen, Maria; Laux, Jeffrey; Sickbert-Bennett, Emily; Anderson, Deverick; Sexton, Daniel; Weber, David J
Abstract: Background: Continuous disinfection of the hospital surface environment may be ideal for infection prevention since the environmental surfaces are repeatedly contaminated with healthcare-associated pathogens. We used light-emitting diode (LED) disinfection technology to investigate its germicidal activity as continuous room decontamination against multidrug-resistant organisms (MDROs) and Clostridium difficile . Methods: We assessed an overhead LED disinfecting system (Vital Vio, high-intensity narrow-spectrum light, 405 nm wavelength) for five test organisms: methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), MDR- Acinetobacter baumannii, carbapenem-resistant Enterobacteriaceae (CRE) and C. difficile spores. Formica test surfaces were inoculated and spread with an estimated 100–500 CFU of each test organism. Triplicate samples were collected with Rodac plates on the Formica at times 0, 1, 3, 6, 24, 48, 72, and 96 hours in each of the LED treatment and control. Two experimental trials were performed. We fit a mixed effects negative binomial model with a log link to the number of colony forming units (CFUs) of the test organisms. Our primary test was of the three-way interaction of treatment by pathogen by time within the full model, followed by tests of the treatment by time interactions within each of the pathogens. Results: The change in mean CFUs diverged by treatment over time, but did so differently by organism ( P < 0.001; Figure 1). Compared with control, the LED treatment led to a significant decline for MRSA ( P < 0.001), VRE ( P < 0.001), and MDR- Acinetobacter ( P < 0.001), but there is insufficient evidence that the treatment made a difference in the mean CFUs of CRE ( P = 0.40) and C. difficile ( P = 0.45). It is clear that more rapid and dramatic decreases occur with the LEDs for MRSA, VRE, and MDR- A. baumannii, compared with control. Although higher counts were observed for C. difficile with the treatment, this was not significant. Conclusion: Our study demonstrated germicidal inactivation of some healthcare-associated pathogens (i.e., MRSA, VRE, MDR- Acinetobacter ) with the continuous LED disinfection. This technology may have promise for decontamination of the healthcare environment. Disclosures: D. Sexton, Centers for Disease Control and Prevention: Grant Investigator, Grant recipient. Centers for Disease Control and Prevention Foundation: Grant Investigator, Grant recipient. UpToDate: Collaborator, Royalty Recipient. D. J. Weber, PDI: Consultant, Consulting fee